A voyage to the Pacific Ocean [electronic resource] : undertaken by command of His Majesty, for making discoveries in the northern hemisphere : performed under the direction of Captains Cook, Clerke, and Gore, in the years 1777, 1778, 1779, 1780. - Cook, James, 1728-1779; Phipps, Constantine John, 1744-1792.; Phillip, Arthur, 1738-1814. The voyage of Governor Phillip to Botany Bay. (Newcastle : Printed by M. Brown ., 1790)
Volume I has title: Captain Cook's voyages round the world. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 17751-17753. Includes Cook's third voyage, Phipps's voyage to the North Pole, and Governor Phillip's voyage to Botany Bay. The account of Phipps's voyage is by an anonymous author and is not to be confused with Commodore Phipps's journal of the same expedition, entitled "A voyage towards the North Pole" (Cf. National Union Catalog pre-1956 imprints). "Vol. II." "The narrative is written partly in the 1st person, following Cook's journal, and partly in the 3rd person, paraphrased from the official account ." (Cf. New South Wales. Public Library, Sydney. Mitchell Library. Bibliography of Captain James Cook. Sydney, 1928, p. 10)--National Union Catalog pre-1956 imprints. "Directions to the binder, for placing the plates in Cook's Voyages"--Colophon. Electronic reproduction. Mode of access: Internet. 44